What Price Fairness? A Bargaining Study - Zwick, Rami; Chen, Xiao-Ping (Management Science, 1999)
Our study concerns bargaining behavior in situations where one party is in a stronger position than the other. We investigate both the tradeoff the favored party makes between pursuing his strategic advantage and giving weight to other players' concern for fairness, and the tradeoff the disadvantaged player makes between pursuing a fair outcome from a disadvantaged position and the cost of that pursuit. In particular, we hypothesize that the degree to which strategically strong players attempt to exploit their strategic advantage depends on their potential costs for doing so. Similarly, the degree to which weak players persist in seeking “fairness” is also a function of how much it (potentially) costs them to do so. Students negotiated in pairs over the division of $HK50 using a finite horizon, fixed-cost (per rejection) alternating offer rule. Each pair consisted of a high-cost and a low-cost bargainer. In accordance with the hypothesis, the willingness of the high-cost bargainers to demand fairness and to persist in their demands was a function of how much it cost them to do so, and the degree to which the low-cost bargainers attempted to exploit their strategic advantage depended on their own cost of rejection. We conclude that “fairness” has a price such that the higher its price, the lower the “demand” for it. This suggests that demands for fairness are subject to cost-benefit evaluation, are in this sense deliberate, and are well thought out.